1999
DOI: 10.1038/sj.sc.3100871
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of `low risk' and `high risk' dives by young adults: risk reduction in spinal cord injury

Abstract: Study design: To establish benchmark normative data for dive entries performed by young adults of the age range most likely to sustain a diving spinal cord injury. Data acquired from analysis of the dives performed, along with survey information, were used to determine which factors make the most contribution to the level of risk in diving. Objectives: To identify in¯uential variables which could contribute to risk of spinal cord injury for each of four types of dives. The types of dives investigated were: div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 8 publications
3
47
0
3
Order By: Relevance
“…However, many people are often unaware of other disastrous consequences surrounding these practices. 1 After death, spinal cord injuries (SCIs) are the most devastating result of water sports accidents, with regard to morbidity, permanent disability and cost. 2 In the United…”
Section: Introductionmentioning
confidence: 99%
“…However, many people are often unaware of other disastrous consequences surrounding these practices. 1 After death, spinal cord injuries (SCIs) are the most devastating result of water sports accidents, with regard to morbidity, permanent disability and cost. 2 In the United…”
Section: Introductionmentioning
confidence: 99%
“…Blanksby, Wearne, and Elliott (1996) suggest that the "vulnerability of the head when diving must be counteracted by children keeping the thumbs clasped and the upper limbs extended overhead at all times" (p. 83). Further, Blitvich, McElroy, Blanksby, and Douglas (1999) stated that "the level of risk in any dive entry can be reduced if the diver keeps the hands together and the arms extended beyond the head" (p. 558). While studying first-year university students with varied swimming and diving backgrounds, Blitvich et al (1999) found that during one out of four dives, the swimmer "pulled both arms backward before or at maximum depth, thus leaving their head totally unprotected" (p. 558).…”
Section: Steps Used To Teach the Racing Startmentioning
confidence: 99%
“…Further, Blitvich, McElroy, Blanksby, and Douglas (1999) stated that "the level of risk in any dive entry can be reduced if the diver keeps the hands together and the arms extended beyond the head" (p. 558). While studying first-year university students with varied swimming and diving backgrounds, Blitvich et al (1999) found that during one out of four dives, the swimmer "pulled both arms backward before or at maximum depth, thus leaving their head totally unprotected" (p. 558). While the authors concluded that this acts to increase the level of risk, the degree to which the head is protected by maintaining proper streamline technique has not been verified.…”
Section: Steps Used To Teach the Racing Startmentioning
confidence: 99%
“…The first part of the rules above, the minimum water depth, has been the subject of reasonably extensive debate within the swimming and scientific communities (Welch & Owens, 1986;Counsilman, Nomura, Endo, & Counsilman, 1988;Blanksby, Wearne, & Elliott, 1996;Gehlsen & Wingfield, 1998;Blitvich, McElroy, Blanksby, & Douglas, 1999;Blitvich, McElroy, Blanksby, Clothier, & Pearson, 2000a;and Blitvich, McElroy, & Blanksby, 2000b;Cornett, White, Wright, Willmott, & Stager, 2010, 2011a, 2011b, 2011c, 2011d, 2012aCornett, White, Wright, & Stager, 2012b, 2014Cornett, Naganobori, & Stager, 2012c;White, Cornett, Wright, Willmott, & Stager, 2011;Stager, Cornett, & Naganobori, 2013). The second aspect of the rules, the distance from the wall for which the minimum water depth must be maintained, has not received much discussion.…”
Section: Indiana Universitymentioning
confidence: 99%